Analysis of User Reviews on the Use of Fintech Dana Syariah - Fauzi Arif Lubis (International Journal of Science and Society, 2023)
Sharia fintech is a form of financial technology that is growing rapidly in Indonesia. This study aims to analyze how users' perceptions and preferences regarding the application fintech Dana Syariah. The method used is the descriptive analysis of data consisting of 100 user reviews that have used fintech Dana Syariah from the Google Play Store. The results of this study are that the majority of respondents have positive reviews of the application. Reviews are grouped into 4 categories consisting of 2 positive categories namely ease of use and friendly service and 2 negative categories namely difficulty using the application and difficult verification.